Estudio y diseño de sistema de agua potable a bombeo para la comunidad Gampala Torobamba, dela parroquie Sicalpa Canton Colta Provincia de Chimborazo. - Lopez Reyes, Santiago Israel (2017)
This work has been made as a contribution to the community "Gampala Torobamba" this community is located 46 kilometers from the Colta canton in the province of Chimborazo. The study was initiated by collecting information through a survey of community dwellers to find the existing needs and problems; currently 70% of the community lacks a system of drinking water supply, so that its inhabitants are concerned about the high risk of contracting infectious diseases by not consuming treated water. It is known that water is one of the essential elements for the survival of all known forms of life. It is so significant that it has been declared a fundamental right for human beings. In the particular case of humans, water is important and must be directly ingested, so it must be potable and suitable for consumption by society, it is important to emphasize that the main source of income in the community is agriculture and Livestock so water is also closely related to the social and economic development of its inhabitants. It is proposed to carry out the study and design of a pumping system that guarantees the supply of vital liquid to the 23 existing homes in the community, thus contributing to the social, economic and tourism development of the sector. The lifetime of the system will be designed for 20 years with a final population of 206 beneficiaries. The technical field work was based mainly on the socio-economic study, topographical survey of the area by total station, inspection of the source of water supply, sampling and sampling for physical, chemical and bacteriological analysis. After the collection of field information, the technical work of the office was continued, for which the following parameters were calculated: design population, water supply, design flows, calculation of the pump, as well as Drafting plans, budget and timeline valued. With the results obtained a work is proposed for filter bed collection of the water source, a pumping station for the transport of water to a treatment and storage plant. The distribution of water was carried out by the EPANET program, which guarantees the required demand and a correct functioning of the distribution network, which will be opened, by gravity and with a PVC pipe. With the contribution of the Study of Environmental Impacts, it is concluded that there is no negative impact of consideration, since the construction of the required infrastructure does not affect either the flora or the fauna of the ecosystem.